Validation of a Comprehensive Set of Pruritus Assessment Instruments: The Chronic Pruritus Tools Questionnaire PRURITOOLS - Emely Verweyen; Sonja Ständer; Kiana Kreitz; Inga Höben; Nani Osada; Marvin Gernart; Claudia Riepe; Manuel Pereira; Christine Blome; Matthias Augustin; Claudia Zeidler (Medical Journals Sweden, 2019)
Few studies have validated standard measurement instruments for evaluation of chronic pruritus. The Chronic Pruritus Tools Questionnaire PRURITOOLS assembles a set of instruments for the assessment of pruritus, such as the visual analogue scale (horizontal 100-mm line), numerical rating scale (0-10), verbal rating scale, and information on pruritus quality and improvement during therapy. This study, with 40 subjects, analysed PRURITOOLS regarding convergent validity and test-retest reliability (60 min), followed by a feasibility questionnaire. Test-retest reliability for PRURITOOLS items was excellent (intraclass correlation coefficient 0.84-1). Strong to very strong correlations between the pruritus intensity scales indicated convergent validity. The feasibility questionnaire showed an overall acceptance of PRURITOOLS, and the majority of subjects (82.5%) considered it an appropriate questionnaire to measure pruritus. In conclusion, PRURITOOLS offers validated tools for rapid pruritus assessment in routine care or endpoints of clinical trials.